A Simple Homoleptic Gallium(I) Olefin Complex: Mimicking Transition‐Metal Chemistry at a Main‐Group Metal?. Issue 1 (27th October 2020) - Glootz, Kim; Barthélemy, Antoine; Krossing, Ingo
Abstract: The earth‐metal olefin complex [Ga I (COD)2 ] + [Al(OR F )4 ] − (COD=1, 5‐cyclooctadiene; R F =C(CF3 )3 ) constitutes the first homoleptic olefin complex of any main‐group metal accessible as a bulk compound. It is straight forward to prepare in good yield and constitutes an olefin complex of a main‐group metal that—similar to many transition‐metals—may adopt the +1 and +3 oxidation states opening potential applications. Crystallographic‐, vibrational‐ and computational investigations give an insight to the atypical bonding between an olefin and a main‐group metal. They are compared to classical transition‐metal relatives. Abstract : The yet underdeveloped coordination chemistry of Ga I species won a new addition to their family. With an unprecedented bonding situation in main‐group chemistry, the complex salt Ga(COD)2 + [Al(OR F )4 ] − (COD=1, 5‐cyclooctadiene; R F =C(CF3 )3 ) offers novel options. Its properties are compared with respect to those of related transition‐metal species.